2023
DOI: 10.3390/cancers15071959
|View full text |Cite
|
Sign up to set email alerts
|

Novel Immunotherapeutic Approaches to Treating HPV-Related Head and Neck Cancer

Abstract: Head and neck cancer (HNC) is the seventh most common malignancy, with oropharyngeal squamous cell carcinoma (OPSCC) accounting for a majority of cases in the western world. While HNC accounts for only 5% of all cancers in the United States, the incidence of a subset of OPSCC caused by human papillomavirus (HPV) is increasing rapidly. The treatment for OPSCC is multifaceted, with a recently emerging focus on immunotherapeutic approaches. With the increased incidence of HPV-related OPSCC and the approval of imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 115 publications
0
9
0
Order By: Relevance
“…The presence of HPV in HNCs significantly alters the disease’s prognosis and therapeutic approach. HPV-positive HNCs typically present with a better response to standard treatment modalities like radiotherapy and chemotherapy, leading to an overall better prognosis compared to HPV-negative cases [ 65 ]. This is primarily attributed to the distinct biological behavior of HPV-positive tumors, which tend to be more sensitive to radiation and cytotoxic agents.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of HPV in HNCs significantly alters the disease’s prognosis and therapeutic approach. HPV-positive HNCs typically present with a better response to standard treatment modalities like radiotherapy and chemotherapy, leading to an overall better prognosis compared to HPV-negative cases [ 65 ]. This is primarily attributed to the distinct biological behavior of HPV-positive tumors, which tend to be more sensitive to radiation and cytotoxic agents.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional standard-of-care therapies often induce significant morbidities such as nerve damage, salivary gland damage, tooth damage, and dysphagia, thus substantially reducing the quality of life of these relatively young and healthy individuals [ 57 , 58 ]. Currently explored de-escalation strategies involve omittance of chemotherapy, reduced radiation doses, and transoral robotic surgery (TORS) for minimally invasive, tissue-sparing resections, as well as incorporation of immunotherapeutic treatment modalities [ 59 , 60 ]. Notably, the first randomized de-escalation trials showed a clear detriment in survival in a subset of patients when chemotherapy was omitted or simply substituted with cetuximab [ 61 , 62 ].…”
Section: Hpv+ Hnscc: a Distinct Form Of Hnscc And Hpv-associated Cancermentioning
confidence: 99%
“…These differences in VEGF expression appear to be partly mediated by HPV-E5/E6 oncoproteins in HPV-related cervical cancer ( 30 ), though the mechanism in HPV-related SCCHN is currently less clear. The increasing incidence of HPV-related SCCHN ( 31 ) has led to further study into targeted therapies tailored to markers unique to HPV-related disease ( 5 ).…”
Section: Vegf In Scchnmentioning
confidence: 99%
“…Mainstays of treatment have historically been a combination or sole approach of chemotherapy and/or radiation, with surgical approaches primarily restricted to locoregional disease ( 3 ). More recently, novel systemic therapies and immunotherapeutics promise change to this treatment paradigm ( 4 ) with certain treatments, such as T-cell associated therapeutics, specifically targeting human papillomavirus (HPV) related disease ( 5 ).…”
Section: Introductionmentioning
confidence: 99%